ANALYSIS OF FAMILY NURSING CARE THROUGH THE INTERVENTION OF EUCALYPTUS OIL INHALATION AND HONEY GINGER DRINKS FOR TODDLERS EXPERIENCING ACUTE RESPIRATORY TRACT INFECTION IN RW 001 GROGOL VILLAGE, DEPOK CITY - Anggraini, Nourmayansa Vidya; Asmarany , Nabilla (Universitas Airlangga, 2025)
Introduction: ARI (Acute Respiratory Infection) is one of the most common problems experienced by toddlers. Symptoms such as cough with phlegm or dry cough and nasal congestion are clinical manifestations of ARI. This paper aims to determine the effect of eucalyptus oil inhalation therapy and the provision of ginger honey drink on toddlers ARI in RW 001 Grogol Village, Depok City. Method: Eucalyptus oil inhalation therapy and honey ginger drink administration were carried out for 3 meetings, where each meeting was carried out inhalation for ± 10-15 minutes and continued by giving honey ginger drink. Results: After the intervention, the results showed that there was a decrease in the sound of ronkhi in the lung lobe and the appearance of mucus coming out of the airway,, indicating that eucalyptus oil inhalation therapy and honey ginger drink can reduce ARI symptoms. It can be concluded that the provision of eucalyptus oil inhalation therapy interventions and ginger honey drinks can reduce ARI in toddlers. Conclusion: therefore community nurses are expected to provide complementary ARI therapy procedures to parents so that parents can apply the therapy when their toddler experiences ARI.